The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15386/mpr-1384
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological spectrum of cutaneous sarcoidosis: an experience from a government institute in North India

Abstract: Background and aims. Sarcoidosis is a multisystem granulomatous disease of unknown etiology and cutaneous involvement is the second most frequent manifestation in systemic sarcoidosis. The aim of the present study is to evaluate the clinical and pathological spectrum of cutaneous sarcoidosis and compare the same with literature available. Methods. The present retrospective study was conducted from January 2010–March 2015 and fifteen cases diagnosed as cutaneous sarcoidosis on biopsy were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, epidermal changes such as atrophy and thinning are frequent features seen in 50% of cases [ 15 ]. Common imitators such as tuberculosis, leprosy, and fungal agents are generally ruled out by applying special stains, such as AFB, PAS, and reticulin [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, epidermal changes such as atrophy and thinning are frequent features seen in 50% of cases [ 15 ]. Common imitators such as tuberculosis, leprosy, and fungal agents are generally ruled out by applying special stains, such as AFB, PAS, and reticulin [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it should be considered in the differential diagnoses while evaluating a patient with an enlarging or aggravated pre-existing scar [ 17 ]. A case study by Singh et al revealed that a foreign body at the site of a tattoo initiated the granuloma formation, which led to the development of a sarcoid lesion [ 1 ]. Moreover, several studies have shown that sarcoidosis-specific lesions commonly arise in pre-existing scars, tattoos, and surgical sites due to long-standing trauma [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by the formation of granulomas and most commonly occurs in the lungs, lymph nodes, and skin. Less often, other organs are affected such as the brain, eyes, heart, and liver [112][113][114]. Malignancy-associated sarcoidosis can be related to either the cancer or the treatment for the neoplasm [73,74,115].…”
Section: Systemic Diseases Sarcoidosismentioning
confidence: 99%